Higher Rate Secret Key Formation (HRKF) based on Physical Layer for Securing Vehicle-to-Vehicle Communication - Dewi, Inka Trisna; Sudarsono, Amang; Kristalina, Prima; Yuliana, Mike (Politeknik Elektronika Negeri Surabaya (PENS), 2020)
One effort to secure vehicle-to-vehicle (V2V) communication is to use a symmetrical cryptographic scheme that requires the distribution of shared secret keys. To reduce attacks on key distribution, physical layer-based key formation schemes that utilize the characteristics of wireless channels have been implemented. However, existing schemes still produce a low bit formation rate (BFR) even though they can reach a low bit error rate (BER). Note that V2V communication requires a scheme with high BFR in order to fulfill its main goal of improving road safety. In this research, we propose a higher rate secret key formation (HRKF) scheme using received signal strength (RSS) as a source of random information. The focus of this research is to produce keys with high BFR without compromising BER. To reduce bit mismatch, we propose a polynomial regression method that can increase channel reciprocity. We also propose a fixed threshold quantization (FTQ) method to maintain the number of bits so that the BFR increases. The test results show that the HRKF scheme can increase BFR from 40% up to 100% compared to existing research schemes. To ensure the key cannot be guessed by the attacker, the HRKF scheme succeeds in producing a key that meets the randomness of the NIST test.